Peningkatan Daya Saing Produk Melalui Pendampingan Sertifikasi Halal Pada UMKM Menyenk Cafe - Novita Sari Hamidaya; Ratih Mukti Azhar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Menyenk Cafe is a micro, small and medium food and beverage business located in Tenggilis Mejoyo Village, Tenggilis Mejoyo District, Surabaya City. The owner of Menyenk Café Umkm still needs assistance to perfect his product. This is done by providing protection standards to safeguard the products sold. Therefore, the UPN